2015
DOI: 10.1001/jamadermatol.2015.121
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Malignant Neoplasms in Hematopoietic Cell Transplant Recipients

Abstract: Given the increased risk of cutaneous malignant neoplasms in hematopoietic cell transplant recipients, this population should be educated on skin self-examination and pursue regular follow-up with dermatologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 38 publications
4
42
2
6
Order By: Relevance
“…10,21 This finding was recently confirmed in a systematic review on cutaneous malignant neoplasms in HSCT recipients. 24 For patients undergoing allogeneic HSCT, TBI is often part of the conditioning regimen (67% in our study), whereas RTRs are not exposed to TBI. Furthermore, TBI is not part of the conditioning regimen for autologous HSCT in Denmark.…”
Section: Discussionmentioning
confidence: 82%
“…10,21 This finding was recently confirmed in a systematic review on cutaneous malignant neoplasms in HSCT recipients. 24 For patients undergoing allogeneic HSCT, TBI is often part of the conditioning regimen (67% in our study), whereas RTRs are not exposed to TBI. Furthermore, TBI is not part of the conditioning regimen for autologous HSCT in Denmark.…”
Section: Discussionmentioning
confidence: 82%
“…The link between skin cancer development and immunosuppression is well established and thus the finding that 35% ( n =36) of cases were NMSCs is not surprising. 21 The 3-year cumulative incidence of SPM falls to 2.9% when NMSCs are excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of these patients survive, they suffer from multiple occurrences, disfigurement and increased expense for health care (31). In a systemic review of 18 studies, the reported median interval to diagnosis after hematopoietic cell transplantation ranged from 7.3 to 9.4 years for BCC and the 20-year cumulative incidence was 6.5% (32). Many of these patients received preconditioning total-body irradiation (TBI) as a preparation for hematopoietic cell transplantation (33).…”
Section: Introductionmentioning
confidence: 99%